2005
DOI: 10.1152/jn.00339.2005
|View full text |Cite
|
Sign up to set email alerts
|

Synaptically Released and Exogenous ACh Activates Different Nicotinic Receptors to Enhance Evoked Glutamatergic Transmission in the Lateral Geniculate Nucleus

Abstract: activation of nicotinic acetylcholine receptors (nAChRs) on glutamatergic transmission in the ventral lateral geniculate nucleus (LGNv) were examined in chick brain slices. Whole cell recordings showed that monosynaptic postsynaptic currents (PSCs) evoked in LGNv neurons by optic tract stimulation were blocked by glutamate receptor antagonists. Exogenously applied nicotine (0.5 M), choline (1 mM), or acetylcholine (ACh, 100 M) markedly increased (Ͼ3-fold) these evoked PSCs. Potentiation by ACh was dose-depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 49 publications
1
22
0
Order By: Relevance
“…Synaptically released glutamate, serotonin, acetylcholine and other neurotransmitters have been studied in detail (Webster, 2001). However, very little in vivo information has been available about the origin and function of the pool of glutamate (Baker et al, 2002;Timmerman and Westerink, 1997), serotonin (Adell et al, 2002), acetylcholine (David and Pitman, 1982;Descarries et al, 1997;Guo et al, 2005) and other neurotransmitters which appear to be present in micromolar concentrations in the extracellular space outside the synaptic cleft (Nyitrai et al, 2006). Our results support one hypothesis in that extracellular neurotransmitters may be involved in shaping synaptic activity in vivo (Baker et al, 2002;Timmerman and Westerink, 1997;Coggan et al, 2005).…”
Section: G H)supporting
confidence: 79%
“…Synaptically released glutamate, serotonin, acetylcholine and other neurotransmitters have been studied in detail (Webster, 2001). However, very little in vivo information has been available about the origin and function of the pool of glutamate (Baker et al, 2002;Timmerman and Westerink, 1997), serotonin (Adell et al, 2002), acetylcholine (David and Pitman, 1982;Descarries et al, 1997;Guo et al, 2005) and other neurotransmitters which appear to be present in micromolar concentrations in the extracellular space outside the synaptic cleft (Nyitrai et al, 2006). Our results support one hypothesis in that extracellular neurotransmitters may be involved in shaping synaptic activity in vivo (Baker et al, 2002;Timmerman and Westerink, 1997;Coggan et al, 2005).…”
Section: G H)supporting
confidence: 79%
“…Throughout this study, all bath solutions contained 10 μM bicuculline to block GABA A receptor-mediated responses and 50 μM AP5 to block NMDA receptors. Previous work demonstrated that >95% of the optic tract-evoked glutamatergic response under these conditions was mediated by non-NMDA receptors (Guo et al, 2005). Bath application of ACh (100 μM for 2 min) had a biphasic effect on optic tract-evoked PSCs.…”
Section: Resultsmentioning
confidence: 95%
“…Because the optic tract is well-delineated in fresh brain slices, it is possible to selectively stimulate the retinal ganglion cell axons. Optic tract stimulation elicits monosynaptic glutamatergic PSCs in LGNv principal neurons that are mediated almost entirely by non-NMDA receptors, and these evoked responses are increased by exogenous nicotinic agonists (Guo et al, 2005). There is also more direct evidence that the cholinergic fibers within the LGNv modulate retinogeniculate transmission.…”
mentioning
confidence: 99%
See 2 more Smart Citations